Using visual evidence - Howells, Richard; Matson, Robert W. 1947- (McGraw-Hill/Open University Press, 2009)
The book shows students, scholars and researchers how to read the visual media to elicit meaning. As primary sources, visual texts can be studied not only for what is directly depicted in the painting or film but also for what it tells us about the people, cultures and societies that made them.